Megaeventos e a conformação de uma identidade nacional: a Copa do Mundo como dispositivo de memória - Paula Ziviani (2016)
This research intends to discuss the use of local and national memories and their mobilization during specific moments in history, highlighting the sports mega-events in Brazil and more specifically the 2014 FIFA World Cup. We therefore analyze symbolic and discursive elements used to represent an imagined nation, making sense to both the internal and external publics in a competitive context of space production for the implementation of transnational events. We investigated which elements of national memory where employed and resignified in shaping of a national identity during the World Cup, and how they were used. The starting point was the understanding that the mega-events are of great strategic value, since they promote the image of the host country internationally. These are mass public directed events with highly global media visibility which explore the symbolic elements of the country social memory. The mega-events affect the large publics lives, dreams, memories, and time due to its ability to dramatize and globalize the present as a media event. The subject was investigated from the notion of Foucaults dispositive, understanding the sports mega-events as catalysts, that is, as something able to articulate heterogeneous elements in an intricate interplay of interacting forces. Based on the concept of the dispositive as theoretical and methodological foundation, and the idea of the myth of racial democracy and cordiality as homogeneous representations of the Brazilian people, a network that could be weaved between heterogenous elements related to the country collective memory was established. Among the results, it is possible to highlight the understanding of the World Cup as a memory dispositive which exhibiting fragments of its national memory elements, instigates the double behavior of remembering and forgetting inherent in the recall process, in addition to the possibility of taking memory as media, in a mediation process, producing significance andstructuring the meaning, as well as establishing various temporalities, modeling and ordering interaction processes.